The Relationship of Knowledge Level of Undernourished Mothers in Toddler Nutritional Pattern Intake in Ciledug Public health center - Hj. Sumarmi Sumarmi; Albahra bin Ladjamuddin (Akademi Keperawatan RSPAD Gatot Soebroto, 2020)
This study aims to determine the relationship between the level of knowledge of undernourished mothers in the nutritional pattern intake of children under five at Ciledug Health Center in 2019. This study uses primary data with quantitative research methods and cross sectional design and uses random sampling techniques. The results showed that there was a significant relationship between work, income, infectious diseases, utilization of health services and the level of maternal knowledge on the nutritional pattern intake of children under five.